2019
DOI: 10.1021/acs.langmuir.9b00736
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl–PEG–Phosphonic Acid-Stabilized Superparamagnetic Manganese Oxide-Doped Iron Oxide Nanoparticles with Synergistic Effects for Dual-Mode MR Imaging

Abstract: The T 1–T 2 dual-mode contrast agents for magnetic resonance imaging (MRI) can generate self-complementary confirmed T 2 and T 1 images, hence greatly improving the reliability. Facilely synthesizing nanoparticles with the ultrasensitive contrast property remains extremely challenging in nanoscience. Moreover, uncovering the mechanism correlating the signal enhancements and chemical constituents is vital for designing novel efficient synergistically enhanced T 1–T 2 dual-mode MRI nanoprobes. Herein, we report … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…A promising T 1 -T 2 dual-mode contrast agent for MRI was developed in a recent study, consisting of superparamagnetic manganese oxide-doped iron oxide (Fe 3 O 4 /MnO) nanoparticles of approximately 20 nm stabilized with hydroxyl− PEG-phosphonic acid [ 199 ]. The T 1 -T 2 weighted images—obtained using a 0.5 T MRI scanner—validated the dual-mode contrast ability on phantoms.…”
Section: Surface Shell Engineering Of Magnetic Materials For Imaging Purposesmentioning
confidence: 99%
See 1 more Smart Citation
“…A promising T 1 -T 2 dual-mode contrast agent for MRI was developed in a recent study, consisting of superparamagnetic manganese oxide-doped iron oxide (Fe 3 O 4 /MnO) nanoparticles of approximately 20 nm stabilized with hydroxyl− PEG-phosphonic acid [ 199 ]. The T 1 -T 2 weighted images—obtained using a 0.5 T MRI scanner—validated the dual-mode contrast ability on phantoms.…”
Section: Surface Shell Engineering Of Magnetic Materials For Imaging Purposesmentioning
confidence: 99%
“…Therefore, we described only silica and PEGylation strategies in this section, since our group has contributed to this field. Thermal decomposition PEG MRI [190][191][192] MRI/SPECT ( 99m Tc) [193] MRI/SPECT ( 125 I) [106,194] MRI/PET ( 68 Ga) [195] MRI/PET ( 64 Cu) [196] MRI/PET ( 71 As) [197] SPECT ( 99m Tc) [174] [198] Hydroxyl−PEG−Phosphonic Acid [199] DSPE-mPEG 2000 /DSPE-mPEG 2000 amine MRI/PET ( 68 Ga) [200] Silica MRI [201,202] MRI/US [203] Mesoporous Silica MRI [202,204] MRI/Fluorescence Imaging [190] Silica MRI/Optical (FITC) [205] Hydrothermal…”
Section: Synthetic Biocompatible Polymersmentioning
confidence: 99%
“…Based on this theory, Lu et al [115] embedded Mn 2+ into Fe 3 O 4 NPs with hydroxyl-PEG-phosphonic acid through a one-pot reaction (Fe 3 O 4 /MnO, with a size of 20 nm) to improve synergistically imaging performance with safe and accuracy because Mn 2+ was T 1 -weighted CA [116]. The stability test indicated that the nanoparticles retained a single scattering peak even though their size increased to 35 nm from 21 nm after 21 days in water.…”
Section: Application Of Fe 3 O 4 Doping Other Metals In the Inner Corementioning
confidence: 99%
“…[40][41][42] FTIR 43,44 In addition stretching vibrations near 1060 cm −1 which could be assigned to P−O−C and at 1241 cm −1 referring to PvO were observed showing clearly the successful grafting of PEG-PA on the surface of magnetic NPs. 45 A TEM image of the magnetic NPs used in this study is presented in Fig. 2A.…”
Section: Nanoparticle Characterizationmentioning
confidence: 99%